THE IMPORTANCE OF FINANCING INNOVATIVE PROJECTS IN THE DEVELOPMENT OF MICROECONOMICS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article examines the role of intellectual capital in the development of the knowledge economy. Approaches to determining the essence of intellectual capital are explored, a classification of the types of its reproduction is given, and the role of the integration of science and education in increasing the return of intellectual capital is emphasized.